2012
DOI: 10.1007/s00134-012-2629-6
|View full text |Cite
|
Sign up to set email alerts
|

ICU admission characteristics and mortality rates among elderly and very elderly patients

Abstract: Purpose The effect of advanced age per se versus severity of chronic and acute diseases on the short- and long-term survival of older patients admitted to the intensive care unit (ICU) remains unclear. Methods Intensive care unit admissions to the surgical ICU and medical ICU of patients older than 65 years were analyzed. Patients were divided into three age groups: 65–74, 75–84, and 85 and above. The primary endpoints were 28-day and 1-year mortality. Results The analysis focused on 7,265 patients above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
183
4
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(223 citation statements)
references
References 30 publications
19
183
4
17
Order By: Relevance
“…Most studies about outcomes in very elderly subjects in the ICU were evaluated with people 80 or 85 y of age and older. 1,[7][8][9][10]23,24 In a large cohort from Australia and New Zealand, 1 the cumulative proportion of ICU admissions and the ICU mortality rates of subjects Ն 90 y old were 0.88% and 12.0% lower than ours. The various admission and mortality rates found for very elderly subjects of other studies are probably attributable to differences in study design, geographic/cultural variations, and differences in the study populations, including the definition of very elderly subjects, severity of the acute illness, and treatment intensity.…”
Section: Discussionmentioning
confidence: 68%
“…Most studies about outcomes in very elderly subjects in the ICU were evaluated with people 80 or 85 y of age and older. 1,[7][8][9][10]23,24 In a large cohort from Australia and New Zealand, 1 the cumulative proportion of ICU admissions and the ICU mortality rates of subjects Ն 90 y old were 0.88% and 12.0% lower than ours. The various admission and mortality rates found for very elderly subjects of other studies are probably attributable to differences in study design, geographic/cultural variations, and differences in the study populations, including the definition of very elderly subjects, severity of the acute illness, and treatment intensity.…”
Section: Discussionmentioning
confidence: 68%
“…The SOFA score increased with increasing age and was found to increase with mortality. This study claimed that in patients aged>75 years, mortality might be higher than expected; the need for special care for these patients was emphasized (12).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have confirmed the very poor long-term prognosis of elderly patients admitted to the ICU [2][3][4][5][6][7][8][9] (Table 1). Importantly, factors such as an atypical presentation with delayed diagnosis and treatment, suboptimal management (because guidelines are not tailored for an elderly population), lower physiologic reserve, immuno-senescence coupled with an inadequate immune response, more frequent and earlier treatment limitations, and finally inadequate discharge policies (location, timing) may account for or at least contribute to excess mortality.…”
Section: Available Evidencementioning
confidence: 83%